China needs to complement its "going-out" policy with a "going-in" strategy - Karl P. Sauvant; Victor Z. Chen (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2014)
The authors suggest the main components of a going-in strategy for China's outward FDI, to assuage skeptics, avoid backlash and build trust in host country communities.
Keywords: 330